TAFSIR MODERASI PEMAHAMAN TEKSTUAL AYAT-AYAT JIHADIS - Jaelani, M Irham; Halimatussadiyah, Halimatussadiyah (Manarul Qur'an: Jurnal Ilmiah Studi Islam, 2023)
Violence is something that cannot be tolerated in life. However, they are still many who still carry out of these actions under the pretext of self-defense or in conditions that are unfavorable to one party. Radicalization now hides in the legitimacy of religious understanding which causes a problem for national security in Indonesia. In the realm of praxis, the phenomenon is also worse with the presence of religious groups that have a tendency to understand and act exclusively, explosively, and intolerant to environmental facts consisting of several religions, cultures and social. This research is an analysis of contemporary interpretation and radicalization that has become a global concern in the context of religious issues. The main objective of this research is to explore peaceful solutions to the issues of violence and radicalization. The research conducted an in-depth analysis of various relevant religious interpretations as well as empirical studies involving previously neglected narratives of violence and radicalization. The research method in this article uses the library research method, in this case collecting data and information with the help of various kinds of sources in the library such as related references, similar previous research, articles, and journals related to the problems to be discussed in this study. The data to be obtained from this research is in the form of explanations, long and complete descriptions. The Qur'an in this case becomes a peaceful solution to the conflict and radical religious understanding. The Qur'an states that diversity is a sunnatullah and diversity should be a force to build more complex harmony.